Analisis Pengaruh Host Country terhadap Perusahaan Multinasional: Skandal “Dieselgate” Volkswagen Group di Amerika Serikat - Yoga Alghazi Ahmad; Ika Riswanti Putranti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Bargaining position is an important part in the dynamics of relations between actors in international relations. Bargaining position can be regarded as a connecting bridge for a party to show leverage and to reach the intended outcome or interest. In the case of the